The Author of 4 Maccabees and Greco-Roman Paideia: Facets of the Formation of a Hellenistic Jewish Rhetor - DeSilva, David A. (Bulletin for biblical research, 2016)
It has long been recognized that the author of 4 Maccabees displays a high level of linguistic, literary, and rhetorical skill that plausibly suggests formal education. This study explores the author's literary accomplishment in the light of Greek education, especially at the secondary and tertiary stages. The author is shown to exhibit facility in many of the particular skills nurtured by the progymnasmata, to reflect the kind of cultural knowledge inculcated by the core texts read in the Greek curriculum, and to demonstrate knowledge of philosophical discourse and rhetorical skills typically taught beyond the secondary level of education. While it remains unknown whether the author studied in the general institutions of his city (relying on private venues for his deep acquaintance with Jewish texts and traditions) or in special institutions established by the Jewish community where Greek education and Jewish cultural knowledge could be combined, he stands as an example of a Jewish author who has most certainly been formed by the standard Greek curriculum through some venue.